Contribution of Local Wisdom Values in The Development of Criminal Punishment in The National Criminal Code - Musyahadah Rahmah, Alef; Hapsari Retnaningrum , Dwi (Jurnal Hukum In Concreto, 2025)
The issue of punishment plays a significant role in criminal law, reflecting a nation's socio-cultural value system. The Indonesian nation has a conflict resolution mechanism based on local wisdom, which is essentially living law. In criminal law reform policies, particularly in criminal law, local wisdom values ​​are incorporated into substantive content. The purpose of this paper is to determine the suitability of local wisdom values ​​in criminal law, considering the central socio-political, socio-philosophical, and socio-cultural values, and the contribution of local wisdom values ​​to the development of criminal law in the National Criminal Code. Through a doctrinal approach, using literature studies on secondary data and qualitative analysis, it can be explained that living law is equated with customary criminal law. The local wisdom values ​​that form the substantive content of criminal law in the National Criminal Code align with the central socio-political, socio-philosophical, and socio-cultural values ​​of Indonesian society. The legal contribution that exists within society to criminalization in the National Criminal Code is customary criminal law, as reflected in Article 2 concerning the applicability of customary law, which allows for the imposition of customary sanctions even if the act is not specifically stated in the Criminal Code. Furthermore, Article 66 of the National Criminal Code regulates additional sanctions, of which subparagraph (1) letter f covers one form, namely the fulfillment of local customary obligations.